Rancang Bangun Sistem Pengendalian Biogas Bertekanan pada Biogas Storage Tank System Hasil Purifikasi dengan Metode Water Scrubber System - Arief Abdurrakhman; Anis Wahyumulyaning Tiyas (P3M Politeknik Negeri Indramayu, 2016)
Biogas is a renewable energy potential to be developed in Indonesia. It is based on the increase in the number of household-scale biogas reactor. But the number of biogas reactors currently installed is still not equipped with biogas purification system integrated with the biogas storage tank system. Storage of purified biogas on the tube is required to extend the range of the use of biogas in some areas that have been using biogas as an alternative energy source. Storage tank systems require control systems in a storage tube that could biogas storage mechanism accordance with the maximum capacity of the tube used. This system uses a sensor components MPX5700AP and Arduino microcontroller, LCD display to display pressure readings, and solenoid valve as an actuator. The working principle of this pressure control system that is used to read the sensor value changes of pressure in the biogas storage tank A and B to be sent to the Arduino and a subsequently processed data accordance specified set point. Charging conducted alternately pressurized biogas through a method ON / OFF Valve Selenoid 1,2,3 and 4 on each biogas storage tanks. At the testing that was done we got the result response of pressure control system against time on pressure sensors P2 and P3 value rise time (tr) = 15 s, settling time (ts) = 12 s, whereas for pressure sensors P3 obtained values rise time ( tr) = 14 s, settling time (ts) = 12 s. The test results are static characteristics sensor hysteresis error of 0.00078% and 0.90%.